Etoposide, cisplatin, and sintilimab combined with anlotinib in successful treatment of adrenocortical carcinoma with lung metastasis: a case report - Niu, Wenjing; Zhang, Haimei; Ma, Xuezhen; Liang, Hua; Qiao, Zhongshi; Wang, Zheng; Niu, Lifeng (Frontiers in Oncology, 2024)
Background: Adrenocortical carcinoma (ACC) is a rare malignant tumor that occurs in the adrenal cortex. It has a high degree of malignancy and comparatively poor overall prognosis. Surgery is the standard curative therapy for localized ACC patients. As well as, the combination regimen of etoposide, doxorubicin, cisplatin (EDP) plus mitotane has been considered as the standardized chemotherapy regimen for advanced ACC. However, new effective regimens are emerging for specific conditions in metastatic ACC.Case Presentation: We report a case of a 66-year-old man diagnosed with metastatic ACC who had a large left adrenal mass (110 mm*87 mm) and multiple metastases in both lungs. The patient was treated with EP and sintilimab for six cycles, anlotinib was introduced after the third cycle. Followups after the second to fourth cycles found significantly reduced lung metastases with all imaging examinations indicating Partial Response (PR) status. The patient received maintenance therapy thereafter with sintilimab plus anlotinib. Until recently, the patient's lung metastases and the left adrenal gland area mass(39mm×29mm) have disappeared and no disease progression has been observed. The progression free survival of this patient has been extended to about 31 months, in sharp contrast to a median survival time of 12 months for majority of advanced ACC. The main adverse events during treatment were appetite loss, grade I myelosuppression, revealed only grade I hypertension and grade I hypothyroidism.Conclusion: This case highlights the remarkable response of our patient's ACC to treatment with a novel combination of EP and sintilimab combined with anlotinib. Our findings suggest a safe and more effective combination therapeutic option for patients with patients with adrenocortical carcinoma.